Extraction of rhenium(VII) and palladium(II) from nitric acid solution using N-cyclohexyl-2-pyrrolidone as an extractant. Issue 7 (3rd July 2021) - Takahashi, Yuya; Ikeda, Yasuhisa; Tsukahara, Takehiko
ABSTRACT: Extraction behavior of Pd(II) and Re(VII) from HNO3 aqueous solutions (0.1–5.0 M, M = mol∙dm −3 ) to CH2 Cl2 containing N -cycrohexyl-2-pyrrolidone (NCP, 0.1–2.0 M) as an extractant has been examined. As a result, it was found that distribution ratios ( D ) of Pd(II) and Re(VII) under [HNO3 ] = 3.0 M increase with increasing [NCP] from 0.1 to 2.0 M and that plots of log D vs . log[NCP] show linear relationships with slopes of approximately 2. It was also found that the D values for Pd(II) increase with increasing [HNO3 ] up to 3.0 M and decrease in the higher [HNO3 ] region (<5.0 M) and those of Re(VII) increase with an increase in [HNO3 ] up to 1.0 M and decrease with a further increase in [HNO3 ] (<5 M). From these results, it was suggested that the extraction reactions of Pd(II) and Re(VII) take place with two NCP molecules and compete with the extraction of HNO3 . Moreover, it was clarified that IR spectra (1550–1700 cm −1 ) of CH2 Cl2 solutions containing extracted Pd(II) and Re(VII) species are consistent with that of trans -Pd(NO3 )2 (NCP)2 and similar to that of HReO4 (NCP)2, respectively. From these results, it is proposed that Pd(II) and Re(VII) species in HNO3 aqueous solutions are extracted to CH2 Cl2 phase containing NCP as Pd(NO3 )2 (NCP)2 and HReO4 (NCP)2 .